The crashworthiness performance of the energy-absorbing composite structure—A review - Ahamad Khilji, Irshad; Siti Nadiah, Mohd Saffe; Reddy Chilakamarry, Chaitanya; Siti Aishah, Rusdan (Springer, Singapore, 2022)
The improved energy absorption capacity of composite materials will upgrade people’s safety in accidents. Several parameters affect energy absorption such as fibre type, matrix type, fibre architecture, specimen geometry, processing conditions, fibre volume fraction, and test speed. These parameters influence the composite material-specific energy absorption. The distinct characteristic properties of composites play an essential role in a variety of industries. Automotive applications have attracted worldwide attention due to their rapid use and are expected to increase. This review focuses on understanding the effect of a particular parameter on the energy absorption capability of composites, an analysis of the energy absorption properties of polymer composites. The data from the various researchers are collected and categorised in the field of energy absorption of composites. Many testing methods and refraction types for composites are described.